An Empirical Model of Students Satisfaction and Service Quality of Jahangirnagar University - Hossain, Moyazzem (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Satisfaction is a state felt by a person who has experienced performance or an outcome that fulfill his or her expectation and service quality is an important parameter of educational excellence. This study attempts to examine the relationship between service quality dimensions (tangibility, responsiveness, reliability, assurance and empathy) and students’ satisfaction. The results exhibit that there is a significant correlation among all the constructs with student satisfaction at 1% level of significance. The results also depict that the tangibles factor is the most important factor which includes a group of statements related to the environment and facilities provided by the university. Therefore, this paper will be helpful for institutions in order to enhance the quality of educational services.